PROFIL KEMAMPUAN PENALARAN MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL DIMENSI TIGA - Mu'jizatin Fadiana; Yustrinda Aprilia (Jurnal Riset Pembelajaran Matematika, 2020)
The purpose of this study is to describe the mathematical reasoning ability of students of class X-1 of SMA Negeri 1 Paciran in solving three dimensional problems. This type of research is descriptive qualitative. Data is collected through tests and interviews that are developed based on indicators of mathematical reasoning ability. Data on students' mathematical reasoning ability test results were analyzed by describing the results of student answers. The results showed that the mathematical reasoning ability of students with high mathematical ability classified well in completing three dimensional problems, mathematical reasoning ability of students with mathematical ability was classified as good in completing three dimensional problems while the mathematical reasoning ability of students with low mathematical ability classified as sufficient in completing dimensional problems three.